2013
DOI: 10.3766/jaaa.24.9.10
|View full text |Cite
|
Sign up to set email alerts
|

Screening Test for Auditory Processing (STAP): A Preliminary Report

Abstract: The current study revealed that the four subsections of STAP merged to form three distinct components. Dichotic CV and gap detection formed two independent components while speech perception in noise and auditory memory merged to form a single component. This indicates a possible relationship between auditory memory and speech perception in noise as suggested by Katz (1992). Thus, STAP is able to detect three different components related to auditory processing. The study also indicates that the number of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
(39 reference statements)
1
21
0
3
Order By: Relevance
“…Current studies search for interactive and easily accessible tools as a screening method (7,8) . The challenge is the need for a battery capable of adequately evaluating all the above-mentioned auditory mechanisms involved in CAP (9) , as well as confirmation of its efficacy through comparison with diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies search for interactive and easily accessible tools as a screening method (7,8) . The challenge is the need for a battery capable of adequately evaluating all the above-mentioned auditory mechanisms involved in CAP (9) , as well as confirmation of its efficacy through comparison with diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…24 Thus, in cases of slow auditory input processing, the information presented at the beginning of the communication cannot be kept in the working memory at the point when the last part of the message is processed and, as a result, the whole message may be “forgotten” or not fully understood. 22 Additionally, this interrelationship has already been described in the literature 8 - 10 , 25 as these are tasks performed by neighboring brain regions. 8 An example of this is the hippocampus in its lower medial portion of the anterior temporal lobe.…”
Section: Discussionmentioning
confidence: 90%
“…The literature indicates evidence of attention function impairment in individuals with a history of otitis media, 6 , 7 as well as likely associations between working memory and hearing in a noisy environment. 8 - 10 In addition, a study 11 observed that the executive function shares cognitive mechanisms underlying auditory skills.…”
mentioning
confidence: 99%
“…There is an increase of interest in disorders of the central auditory processing, including the issue of the possible methods of early detection of said disorders [10]. Attempts are taken to examine children under the age of seven with objective methods.…”
Section: Number Of Confirmed Apd Diagnoses Distribution Of Confirmed mentioning
confidence: 99%